VHDL implementation of DES algorithm / Emmanvel Kajan Mering - Emmanvel, Kajan Mering (2004)
This project is about the development of DES in hardware. DES, and it's variants (tripleDES) are the main encryption methods used in industry today. The DES designed should be able to process a 64-bit data block and it's 64-bit key and produces a 64-bit encrypted output. It also acts as decryptor, which is done by entering the 64-bit encrypted data together with the sub-key (operate in decrypt mode, where key is entered in reverse order). In order for our DES to work, modules are designed. These modules are controller, RAM, the DES core (initdata) and sub-key generator. All these submodules are developed, and then integrated as a complete DES cryptosystem. This DES system will be developed using VHSIC Hardware Description Language (VHDL). This is a complete report, from the designing phase up to the system testing at the end.